Overview of Characteristics of Hypertension Patients - Silalahi, Roberth Harnat; Simbolon, Hot Rotua; Silaban, Jojor (Indonesian Journal of Global Health Research, 2024)
Hypertension is called "The Silent Killer", because it often has no symptoms, so sufferers are not aware of their condition before complications arise. According to Riskesdas in 2018 the number of hypertension sufferers in Indonesia was 34.11%. Hypertension can be triggered by several factors, namely age, gender, occupation, BMI, genetics, intake of salty foods and salt, consuming alcohol. Research Objective to determine the characteristics of hypertension sufferers in the working area of ​​the Sumbul Community Health Center, Dairi District in 2024. The type of research is quantitative descriptive research carried out in January - May 2024. The population of this study is 221 people with hypertension, sampling technique used accidental sampling with a total sample of 44 respondents. The way to collect data is by distributing questionnaires. The data is analyzed using bivariate and univariate analysis. Then the data is processed using SPSS. the characteristics of hypertension sufferers are that the majority are aged ≥ 61 years and over, 59.09%, 56.82% are female, the majority of respondents work as farmers, 40.91%, the majority have a fat BMI, 56.82%, the majority do not have a family history of hypertension sufferers as much as 59.09%, the majority consume salty/salt every day as much as 47.73%, the majority did not consume alcohol as much as 59.09%, the majority did not smoke as much as 68.18%, the majority do exercise 3 times a week as much as 43.18%. It is hoped that community health center officers will provide education about hypertension to the community.